Friction nano-generator based on barium strontium zirconate titanate material and preparation method thereof

Through a friction nanogenerator based on barium zirconium titanate material and its preparation method, the problems of complex preparation processes and general output current performance in the prior art are solved, and the effect of simplifying the process and significantly improving the output performance is achieved.

CN119727446APending Publication Date: 2025-03-28XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821316.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The preparation process of existing friction nanogenerators is complex and the output current performance is average, making it difficult to meet the needs of energy collection and environmental monitoring.

Method used

The friction nanogenerator based on barium zirconium titanate material and its preparation method are used to prepare PVA films by PVA aqueous solution method, and BZTS composite materials are prepared by solid phase reaction method, and BZTS/PDMS film is mixed with PDMS, and finally the friction nanogenerator is assembled.

Benefits of technology

The preparation process is simplified, and the output performance of friction nanogenerators is significantly improved, especially the output current performance is optimal, meeting the needs of energy collection and environmental monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119727446A_ABST
    Figure CN119727446A_ABST
Patent Text Reader

Abstract

The invention discloses a friction nano-generator based on a barium strontium zirconate titanate material and a preparation method thereof, and belongs to the technical field of nano-generator preparation, and the preparation method comprises the following steps: S1, preparing a PVA film through a PVA aqueous solution method; s2, preparing a BZTS composite material through a solid-phase reaction method; s3, preparing a BZTS / PDMS thin film; and S4, fixing positive and negative friction layers, and assembling a device to obtain the friction nano-generator. According to the friction nano-generator based on the barium strontium zirconate titanate material and the preparation method of the friction nano-generator, the preparation process is simple, the output performance of the finally prepared friction nano-generator is excellent, the output performance of the friction nano-generator is optimal due to the addition of the BZTS, and particularly, the output current is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanogenerator preparation, and in particular to a friction nanogenerator based on barium strontium zirconate titanate material and a preparation method thereof. Background Art

[0002] With the continuous growth of global energy demand and the gradual depletion of fossil fuel resources, the development of renewable energy and green energy conversion technology has become particularly important. As a technology that can convert mechanical energy in the environment into electrical energy, the triboelectric nanogenerator (TENG) provides new possibilities for energy diversification and sustainable development. Moreover, TENG has the advantages of simple structure, low cost, high energy conversion efficiency, easy miniaturization and diversified applications. Therefore, in recent years, TENG technology has been rapidly developed and widely studied, and its application potential in energy collection, self-powered sensors, wearable devices and other fields has been gradually explored.

[0003] The working mode of the prepared friction nanogenerator is: vertical contact separation mode. The physical mechanism is: when the surfaces of two different materials contact each other and move relative to each other, due to the different electron affinities of the material surfaces, electrons will transfer from one material to another, causing the two surfaces to carry equal but opposite charges. After friction electrification, the two surfaces separate, and since the charges cannot be neutralized immediately, each surface will maintain a certain charge. The charged surface will induce the redistribution of charges in nearby conductors to form a potential difference. If the external circuit is closed at this time, then driven by the potential difference, electrons will flow in the circuit to form a current. When the current in the external circuit flows, the charge on the charged surface will gradually be neutralized. When the two surfaces contact again, the remaining charge will be further neutralized through the external circuit to complete a working cycle.

[0004] As an emerging energy harvesting technology, the improvement of the friction layer material of TENG is of great significance to improving its performance and broadening its application fields. By improving the friction layer material, we can improve the output performance, enhance the stability, and realize the multifunctionality and intelligence of the friction layer material. It has broad development prospects and is expected to bring revolutionary changes to the fields of energy harvesting and environmental monitoring. The preparation process of the existing general friction nanogenerator is complicated, and the output current performance of the final prepared friction nanogenerator is average. Summary of the invention

[0005] The purpose of the present invention is to provide a friction nanogenerator based on barium strontium zirconate titanate material and a preparation method thereof. The preparation process is simple, and the output performance of the friction nanogenerator finally prepared is excellent. The addition of BZTS makes the output performance of the friction nanogenerator optimal, especially the output current is greatly improved.

[0006] To achieve the above object, the present invention provides a method for preparing a friction nanogenerator based on barium strontium zirconate titanate material, comprising the following steps:

[0007] S1, preparing a PVA film by a PVA aqueous solution method;

[0008] S2, preparing BZTS composite materials by solid phase reaction method;

[0009] S3, preparing BZTS / PDMS film;

[0010] S4. Fix the positive and negative friction layers, assemble the device, and obtain the friction nanogenerator.

[0011] Preferably, the specific operation of S1 is:

[0012] S11, slowly pouring the polyvinyl alcohol particles into a beaker filled with deionized water while stirring, placing it in a magnetic stirrer, heating and stirring until the polyvinyl alcohol particles in the deionized water are completely dissolved to obtain a prepared PVA solution;

[0013] S12. Cut the lotus leaves into the same and appropriate size, rinse them and fix them on the bottom of different culture dishes respectively, pour the prepared PVA solution into the culture dishes to completely cover the biomaterial, then perform defoaming treatment, wait for the PVA to solidify at room temperature to obtain a PVA film, separate the PVA film from the biomaterial after solidification, and fix the PVA film on an acrylic template for later use.

[0014] Preferably, the specific operation of S2 is: drying and mixing analytical pure reagents of barium carbonate, titanium dioxide, zirconium dioxide and strontium carbonate, and grinding them thoroughly to obtain barium strontium zirconate titanate BZTS, placing the ground mixture in a crucible and calcining it, after calcination, gradually cooling the sample to room temperature, grinding it again and washing it with a dilute hydrochloric acid solution, drying the washed powder sample in an oven, and grinding it thoroughly again.

[0015] Preferably, the specific operation of S3 is: first, PDMS and a curing agent are mixed, and then BZTS powder with different doping amounts is added to obtain a BZTS / PDMS mixed solution, and then the BZTS / PDMS mixed solution is poured on a PVA film, and the PVA film coated with the BZTS / PDMS mixed solution is placed on a heating table for curing, and peeled off to obtain BZTS / PDMS films with different doping mass percentages.

[0016] Preferably, the specific operation of S4 is: using carbon cloth and cotton as positive electrode friction materials, BZTS / PDMS film as negative electrode material, and copper foil as conductive electrode to construct a friction nanogenerator.

[0017] Preferably, the amount of polyvinyl alcohol in S11 is 10-20 g, the amount of deionized water is 50-100 mL, the heating temperature is 50-100° C., and the stirring is performed for 1-3 h.

[0018] Preferably, in S12, the PVA is kept at room temperature for 24-36 hours to wait for solidification, and the surface microstructure of the PVA film finally obtained is opposite to the surface microstructure of the biological object.

[0019] Preferably, the drying temperature of each reagent in S2 is 50-100°C, the drying time is 1-5h, and the reagents are prepared according to B1Z 0.2 T 0.8 :XSr are uniformly mixed in a stoichiometric ratio, wherein X=3% mol; an agate mortar is used for grinding for 1-3 hours, the mixture is calcined at 500-800°C for 3-6 hours, then at 1000-1500°C for 5-10 hours, the dilute hydrochloric acid washing times are 2-3 times, the final drying temperature is 50-100°C, and the drying time is 10-12 hours.

[0020] Preferably, the mass ratio of BZTS in S3 is 5, 10, 15, 20 wt.%, the mass ratio of PDMS and curing agent is 10:1, the final curing temperature is 80-120° C., and the curing time is 15-45 min.

[0021] The present invention provides a friction nanogenerator based on a barium strontium zirconate titanate material. The friction nanogenerator is prepared by using the above-mentioned method for preparing a friction nanogenerator based on a barium strontium zirconate titanate material.

[0022] Therefore, the present invention adopts the above-mentioned friction nanogenerator based on barium strontium zirconate titanate material and its preparation method. The preparation process is simple, and the output performance of the friction nanogenerator finally prepared is excellent. The addition of BZTS makes the output performance of the friction nanogenerator reach the best, especially the output current is greatly improved.

[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a structural schematic diagram of a friction nanogenerator based on a barium strontium zirconate titanate material and a friction nanogenerator according to an embodiment of the present invention and a method for preparing the same;

[0025] Figure 2 The output voltage of the friction nanogenerator at different frequencies according to the friction nanogenerator based on barium strontium zirconate titanate material and the preparation method thereof in the embodiment of the present invention;

[0026] Figure 3The output voltage and output current of the friction nanogenerator prepared by BZTS with different doping amounts in the friction nanogenerator based on barium strontium zirconate titanate material and the preparation method thereof in the embodiment of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0028] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0029] The present invention provides a friction nanogenerator based on barium strontium zirconate titanate material, using carbon cloth and cotton as positive electrode friction materials, BZTS / PDMS film as negative electrode material, and copper foil as conductive electrode. The preparation method thereof comprises the following steps:

[0030] S1. Preparation of PVA film by PVA aqueous solution method:

[0031] S11. Use an electronic balance to weigh 10-20 g of polyvinyl alcohol particles, and slowly pour into a beaker containing 50-100 mL of deionized water while stirring. Place in a magnetic stirrer, heat at 50-100° C., and stir for 1-3 h until the polyvinyl alcohol particles in the deionized water are completely dissolved to obtain a prepared PVA solution.

[0032] S12. Cut the lotus leaves into the same and appropriate size, rinse them and fix them on the bottom of different culture dishes respectively, pour the prepared PVA solution into the culture dishes to completely cover the biological material, then perform defoaming treatment, keep it at room temperature for 24-36 hours to wait for PVA to solidify to obtain a PVA film, separate the PVA film from the biological material after solidification, the surface microstructure of the PVA film is opposite to the surface microstructure of the biological object, and fix the PVA film on an acrylic template for later use.

[0033] S2. Preparation of BZTS composite material by solid phase reaction method: Dry analytical pure reagents of barium carbonate, titanium dioxide, zirconium dioxide and strontium carbonate at 50-100°C for 1-5h and mix them. 0.2 T 0.8 :XSr (X = 3% mol) in a stoichiometric ratio and fully ground for 1-3h using an agate mortar to obtain barium strontium zirconate titanate BZTS. The ground mixture is placed in a crucible and calcined at 500-800°C for 3-6h, then calcined at 1000-1500°C for 5-10h. After calcination, the sample is gradually cooled to room temperature, ground again, and washed 2-3 times with a dilute hydrochloric acid solution. The washed powder sample is dried in an oven at 50-100°C for 10-12h, and ground again.

[0034] S3. Preparation of BZTS / PDMS film: BZTS / PDMS mixed solutions with different BZTS mass ratios were prepared. First, PDMS and curing agent were mixed in a mass ratio of 10:1, and then BZTS powders with different mass ratios were added to obtain BZTS / PDMS mixed solutions. The mass ratio of BZTS was 5, 10, 15, and 20 wt.%. Then, the BZTS / PDMS mixed solution was poured on a PVA film, and the PVA film coated with the BZTS / PDMS mixed solution was placed on a heating table at 80-120° C. for curing for 15-45 min, and then peeled off to obtain BZTS / PDMS films with different doping mass percentages.

[0035] S4, using carbon cloth and cotton as positive electrode friction materials, BZTS / PDMS film as negative electrode material, copper foil as conductive electrode, fixing positive and negative friction layers, assembling devices, and obtaining a friction nanogenerator, the structure of which is as follows Figure 1 shown.

[0036] Embodiment 1

[0037] The present invention provides a friction nanogenerator based on barium strontium zirconate titanate material, and the preparation method thereof comprises the following steps:

[0038] S1. Preparation of PVA film by PVA aqueous solution method:

[0039] S11. Slowly pour 20 g of polyvinyl alcohol particles into a beaker containing 70 mL of deionized water while stirring, put it into a magnetic stirrer, heat it at 95° C. and stir it for 2 h until the polyvinyl alcohol particles in the deionized water are completely dissolved to obtain the prepared PVA solution.

[0040] S12. Cut the lotus leaves into the same and appropriate size, rinse them and fix them on the bottom of different culture dishes respectively, pour the prepared PVA solution into the culture dishes to completely cover the biological material, then perform defoaming treatment, keep it at room temperature for 36 hours to wait for PVA to solidify to obtain a PVA film, separate the PVA film from the biological material after solidification, the surface microstructure of the PVA film is opposite to the surface microstructure of the biological object, and fix the PVA film on an acrylic template for later use.

[0041] S2. Preparation of BZTS composite material by solid phase reaction method: analytical pure reagents of barium carbonate, titanium dioxide, zirconium dioxide and strontium carbonate were dried at 90°C for 3h and mixed. 0.2 T 0.8:XSr (X = 3% mol) in a stoichiometric ratio and fully ground using an agate mortar for 1-3h. The ground mixture is placed in a crucible and calcined at 600°C for 4h and then at 1250°C for 6h. After calcination, the sample is gradually cooled to room temperature, ground again, and washed 2-3 times with a dilute hydrochloric acid solution. The washed powder sample is placed in an oven and dried at 80°C for 10h, and then fully ground again.

[0042] S3, preparation of BZTS / PDMS film: first, PDMS and curing agent were mixed in a mass ratio of 10:1, and then 5wt.% BZTS powder was added to obtain a BZTS / PDMS mixed solution. Then, the BZTS / PDMS mixed solution was poured on the PVA film, and the PVA film coated with the BZTS / PDMS mixed solution was placed on a heating table at 100°C for 30 minutes for curing, and then peeled off to obtain a BZTS / PDMS film.

[0043] S4. Use carbon cloth and cotton as positive friction materials, BZTS / PDMS film as negative electrode material, copper foil as conductive electrode, fix positive and negative friction layers, assemble devices, and obtain a friction nanogenerator (TENG). Through the triboelectric effect, positive charges are induced on the surface of the positive friction layer and negative charges are induced on the surface of PDMS, thereby realizing the basic friction power generation process of TENG.

[0044] Embodiment 2

[0045] The only difference between this embodiment and the first embodiment is that the doping amount of BZTS in S3 is 10 wt.%, and the other conditions are the same.

[0046] Embodiment 3

[0047] The only difference between this embodiment and the first embodiment is that the doping amount of BZTS in S3 is 15 wt.%, and the other conditions are the same.

[0048] Embodiment 4

[0049] The only difference between this embodiment and the first embodiment is that the doping amount of BZTS in S3 is 20 wt.%, and the other conditions are the same.

[0050] Comparative Example 1

[0051] The only difference between this embodiment and the first embodiment is that the doping amount of BZTS in S3 is 0 wt.%, and the other conditions are the same.

[0052] Figure 2 is the output voltage of the friction nanogenerator at different frequencies. It can be seen from the figure that with the increase of the operating frequency, the output performance of TENG is improved, and the output voltage reaches the maximum under the impact frequency condition of 3Hz.

[0053] TENG generates friction charges through the contact between electrodes, and the friction charges generate current through an external circuit to supply power. The most important parameters that characterize the output performance of TENG are the output voltage and output current generated by TENG. Figure 3 (a) shows the output voltage of TENG when the BZTS doping amount is 5Wt%, 10Wt%, 15Wt% and 20Wt%, respectively. Figure 3 (b) shows the output current of TENG when the BZTS doping amount is 5Wt%, 10Wt%, 15Wt% and 20Wt%, respectively. Figure 3 It can be seen that the output performance of the friction nanogenerator prepared in Examples 1 to 4 is significantly better than the output performance of the friction nanogenerator prepared in Comparative Example 1 without adding BZTS, and when the doping amount is 15 wt%, the output performance of TENG reaches the best, and the output voltage and output current reach 47 V and 236 μA respectively. From the figure, it can be clearly seen that the influence of the BZTS doping amount on the performance of the TENG device, especially the output current has been greatly improved.

[0054] Therefore, the present invention adopts the above-mentioned friction nanogenerator based on barium strontium zirconate titanate material and its preparation method. The preparation process is simple, and the output performance of the friction nanogenerator finally prepared is excellent. The addition of BZTS makes the output performance of the friction nanogenerator reach the best, especially the output current is greatly improved.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a friction nanogenerator based on barium strontium zirconate titanate material, characterized in that: The following steps are involved: S1, preparing a PVA film by a PVA aqueous solution method; S2, using barium zirconate titanate material to prepare BZTS composite material by solid phase reaction method; S3, preparing BZTS / PDMS film; S4. Fix the positive and negative friction layers, assemble the device, and obtain the friction nanogenerator.

2. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 1, characterized in that: The specific operations of S1 are: S11, slowly pouring the polyvinyl alcohol particles into a beaker filled with deionized water while stirring, placing it in a magnetic stirrer, heating and stirring until the polyvinyl alcohol particles in the deionized water are completely dissolved to obtain a prepared PVA solution; S12. Cut the lotus leaves into the same and appropriate size, rinse them and fix them on the bottom of different culture dishes respectively, pour the prepared PVA solution into the culture dishes to completely cover the biomaterial, then perform defoaming treatment, wait for the PVA to solidify at room temperature to obtain a PVA film, separate the PVA film from the biomaterial after solidification, and fix the PVA film on an acrylic template for later use.

3. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 1, characterized in that: The specific operation of S2 is: dry and mix analytical pure reagents of barium carbonate, titanium dioxide, zirconium dioxide and strontium carbonate, and grind them thoroughly to obtain barium strontium zirconate titanate BZTS, put the ground mixture into a crucible and calcine it, after calcination, gradually cool the sample to room temperature, grind it again and wash it with a dilute hydrochloric acid solution, dry the washed powder sample in an oven, and grind it thoroughly again.

4. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 1, characterized in that: The specific operation of S3 is: first, PDMS and a curing agent are mixed, and then BZTS powder with different doping amounts is added to obtain a BZTS / PDMS mixed solution. Then, the BZTS / PDMS mixed solution is poured on a PVA film, and the PVA film coated with the BZTS / PDMS mixed solution is placed on a heating table for curing, and then peeled off to obtain BZTS / PDMS films with different doping mass percentages.

5. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 1, characterized in that: The specific operation of S4 is: using carbon cloth and cotton as positive electrode friction materials, BZTS / PDMS film as negative electrode material, and copper foil as conductive electrode to construct a friction nanogenerator.

6. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 2, characterized in that: The amount of polyvinyl alcohol in S11 is 10-20 g, the amount of deionized water is 50-100 mL, the heating temperature is 50-100° C., and the stirring is performed for 1-3 h.

7. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 2, characterized in that: In S12, the PVA is kept at room temperature for 24-36 hours to wait for solidification. The surface microstructure of the PVA film finally obtained is opposite to the surface microstructure of the biological object.

8. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 3, characterized in that: The drying temperature of each reagent in S2 is 50-100℃, the drying time is 1-5h, and the reagents are in accordance with B1Z 0.2 T 0.8 :XSr are uniformly mixed in a stoichiometric ratio, wherein X=3% mol; an agate mortar is used for grinding for 1-3 hours, the mixture is calcined at 500-800°C for 3-6 hours, then at 1000-1500°C for 5-10 hours, the dilute hydrochloric acid washing times are 2-3 times, the final drying temperature is 50-100°C, and the drying time is 10-12 hours.

9. The method for preparing a friction nanogenerator based on barium strontium zirconate titanate material according to claim 4, characterized in that: The mass ratio of BZTS in S3 is 5, 10, 15, and 20 wt.%, the mass ratio of PDMS and curing agent is 10:1, the final curing temperature is 80-120°C, and the curing time is 15-45 min.

10. A friction nanogenerator based on barium strontium zirconate titanate material, characterized in that: A friction nanogenerator is prepared by using the method for preparing a friction nanogenerator based on a barium strontium zirconate titanate material as described in any one of claims 1 to 9.